EDENT1FI Master Protocol for screening of presymptomatic early-stage type 1 diabetes in children and adolescents - Melanie Gündert; Anette-Gabriele Ziegler; Peter Achenbach; Olga Kordonouri; Agnieszka Szypowska; Ezio Bonifacio; Parth Narendran; Christiane Winkler; R Ribeiro; Sandra Hummel; Przemysława Jarosz-Chobot; Emanuele Bosi; et al. (BMJ Open)
Introduction The identification of type 1 diabetes at an early presymptomatic stage has clinical benefits. These include a reduced risk of diabetic ketoacidosis (DKA) at the clinical manifestation of the disease and a significant reduction in clinical symptoms. The European action for the Diagnosis of Early Non-clinical Type 1 diabetes For disease Interception (EDENT1FI) represents a pioneering effort to advance early detection of type 1 diabetes through public health screening. With the EDENT1FI Master Protocol, the project aims to harmonise and standardise screening for early-stage type 1 diabetes and care.Methods and analysis Public health islet autoantibody screening is conducted in the Czech Republic, Denmark, Germany, Italy, Poland, Portugal, Sweden and the UK. Between November 2023 (start date) and October 2028 (planned end date), an estimated number of 200 000 children and adolescents aged 1–17 years are expected to be screened. Screening is performed in capillary blood, examining different islet autoantibodies (autoantibodies against insulin, glutamic acid decarboxylase-65, insulinoma-associated antigen-2 and/or zinc transporter-8). Positive screening results undergo confirmation through a second antibody method. A second (venous) blood sample is requested if at least two autoantibodies are detected, to confirm the autoantibody status. Children and adolescents with confirmed two or more autoantibodies are invited to metabolic staging (oral glucose tolerance test, haemoglobin A1c (HbA1c), random glucose, optionally continuous glucose monitoring); an educational programme and recommendations for monitoring are provided. The feasibility and acceptability of screening are evaluated by feedback questionnaires. Pseudonymised data is collated in the EDENT1FI Registry. Study outcomes include country-specific screening rates, prevalences of stage 1 and stage 2 type 1 diabetes, number in EDENT1FI Registry, proportion with DKA and symptoms at clinical diagnosis and median HbA1c.Ethics and dissemination Following the EDENT1FI Master Protocol, site-specific protocols are developed and approved by local ethics committees (Technical University of Munich, Medical Faculty, Nr. 70/14; Medizinische Hochschule Hannover, Nr. 9588_BO_S_2021; Technische Universität Dresden, Nr. BO-EK-356082020; Center for Sundhed Region Hovedstaden, Nr. H-22053116; Swedish Ethical Review Authority, Nr. 2023-00312-01; National Health Service Health Research Authority and Health Care Research Wales, IRAS (Integrated Research Application System) project ID 309252; Italian National Institute of Health, National ethics committee for clinical trials of public research bodies (EPR) and other national public institutions, Prot. PRE BIO CE Nr. 0059835; Charles University in Prague, Ethics Committee for Multi-Centric Clinical Trials of the University Hopital Motol and 2nd Faculty of Medicine, Nr. 1271/23; Bioethics Committee at the Medical University of Warsaw, Nr. 21/2024 and KB/6/R/2024; Associação Protectora dos Diabéticos de Portugal, Nr. 211/2024). Results are disseminated through peer-reviewed journals and conference presentations and will be shared openly.